2020
DOI: 10.3390/ijerph17145109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Viewing Video Representation of the Urban Environment and Forest Environment on Mood and Level of Procrastination

Abstract: A common problem among students is the problem of delaying important work activities, which is conceptualized as procrastination. Since procrastination can cause considerable costs for society, we would like to find a method to effectively alleviate the symptoms of this conditioning. It has been proven in an earlier study that staying in the forest environment increases vitality and reduces anxiety, and the negative state of these features can be associated with the intensification of procrastination symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 84 publications
1
23
0
Order By: Relevance
“…The most common scale in the sample was the Profile Of Mood States (POMS), whose purpose is to evaluate individual moods associated with certain forest exposure [ 37 , 38 , 39 ]. The Positive And Negative Affect Schedule (PANAS) is instead one of the oldest but not so popular scales available [ 55 ], and was used by Bielinis et al [ 37 , 51 ] and Park et al [ 36 ] for the evaluation of the therapeutic effects of forests. The evaluation of rest is conducted with a specific scale called the Restoration Outcome Scale (ROS), which is composed of six items [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common scale in the sample was the Profile Of Mood States (POMS), whose purpose is to evaluate individual moods associated with certain forest exposure [ 37 , 38 , 39 ]. The Positive And Negative Affect Schedule (PANAS) is instead one of the oldest but not so popular scales available [ 55 ], and was used by Bielinis et al [ 37 , 51 ] and Park et al [ 36 ] for the evaluation of the therapeutic effects of forests. The evaluation of rest is conducted with a specific scale called the Restoration Outcome Scale (ROS), which is composed of six items [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, looking at a virtual forest landscape is also associated with many benefits that can be derived by the respondents. A good example is a study in which people looking at films from forest areas experienced relaxation, but this also decreased their willingness to procrastinate [ 51 ]. In other studies, looking at a virtual forest reduced stress in adults [ 52 ], and the respondents’ relationships to the virtual forest environment were varied [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of studies have shown the efficacy of attentional strategies such as focusing on relaxing music (Linnemann et al, 2015) or videos of natural environments (Bielinis et al, 2020;J. Freeman et al, 2004;Wang et al, 2020) for reducing stress levels and increasing momentary well-being.…”
Section: Relaxationmentioning
confidence: 99%
“…A growing body of studies have shown the efficacy of attentional strategies such as focusing on relaxing music (Linnemann et al, 2015) or videos of natural environments (Bielinis et al, 2020; J. Freeman et al, 2004; Wang et al, 2020) for reducing stress levels and increasing momentary well‐being. In this regard, VR represents a powerful tool to further foster these strategies because it can provide users with the possibility of experiencing, from a first‐person perspective, a virtual world that integrates pleasant, peaceful, and non‐arousing audio and visual stimuli.…”
Section: What Is the Evidence?mentioning
confidence: 99%